PROGRAM SEKOLAH RAMAH ANAK DALAM PENINGKATAN PRESTASI BELAJAR SISWA DI UPTD SDN 190 BALLERE KECAMATAN KEERA KABUPATEN WAJO - Sumarni Sumarni; Asrijal Asrijal; Rahmawati Rahmawati (Jurnal Manajemen Pendidikan, 2026)
This study aims to examine the implementation of the Child-Friendly School (CFS) program at UPTD SDN 190 Ballere, Keera District, Wajo Regency, identify factors that influence its implementation, and analyze its impact on improving student learning achievement. This research is motivated by the importance of creating a safe, inclusive, and violence-free educational environment as a prerequisite for successful learning and character building in children. The research method used is a descriptive qualitative approach, with data collection techniques through observation, in-depth interviews, and documentation of the principal, teachers, students, and school committee. Data analysis was conducted using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawing, which were verified through triangulation of sources and methods. The results of the study show that the implementation of SRA at UPTD SDN 190 Ballere has been successful thanks to the commitment of the principal, the active involvement of teachers, and the support of parents and the community. The main supporting factors include consistent school policies on SRA principles, the implementation of participatory and empathetic learning, and positive habits such as morning literacy, group exercise, and religious activities. The inhibiting factors include limited infrastructure and differences in understanding among school members.